1998
DOI: 10.1007/s004140050118
|View full text |Cite
|
Sign up to set email alerts
|

Fatal wounds to the thorax caused by gunshots from blank cartridges

Abstract: Lethal injuries of the thorax due to shots fired from blank cartridges calibre 8 mm are reported in three cases. The muzzle of the weapon was in contact with the left side of the breast (contact discharge) and injuries to bones were absent in all three cases. In two of the cases the pericardium was not involved but the anterior wall of the right heart ventricle was ruptured and death was due to cardiac tamponade. In the third case the pericardial sac and the left ventricle were both ruptured and the victim die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
3

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 6 publications
2
15
0
3
Order By: Relevance
“…In the literature, many of publications about blank gun injuries revealed that blank guns could be harmful for the soft tissue and the bone tissue. Our findings were consistent with the literature (1,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). In present study, blank guns caused skin tissue damage, destruction of muscle tissue, burnings and the soot, frequently.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the literature, many of publications about blank gun injuries revealed that blank guns could be harmful for the soft tissue and the bone tissue. Our findings were consistent with the literature (1,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). In present study, blank guns caused skin tissue damage, destruction of muscle tissue, burnings and the soot, frequently.…”
Section: Discussionsupporting
confidence: 93%
“…According to legislations about blank guns in some European countries, blank gun sellers and customers must be informed about the dangers of these weapons (27). In German laws, it is sufficient to have only an identity card while buying one (13). Some countries in Europe, alarming guns, blank cartridge guns and other non-lethal weapons are permitted to adults aged 18 and older (27).…”
Section: Discussionmentioning
confidence: 99%
“…Bu mesafeden yapılan kuru sıkı atışlarda, oluşan basıncın c ld , kem klerde dah l olmak üzere c lt altı yapıları parçalayab lecek kadar büyük olduğu b ld r lm şt r (10). Kuru sıkı atışlar kafatası kem kler nde kırığa sebep olab l rler (1,2,11). Ancak kafatası kem k kırığı olmadan da subdural hematom, subarakno d kanama, kontüzyon ve ntraserebral lezyonlar meydana get reb l rler (1,12).…”
Section: Res M 5-6 Kuru Sıkı S Lah Le B T ş K Atış Sonucu Yaralanaraunclassified
“…This high temperatures of burning gas is thought to be cause flame burn in this patient (Figure 1). Moreover, the high temperature might cause formation of CO-hemoglobin, which is evident by bright red muscle tissue [18]. …”
Section: Discussionmentioning
confidence: 99%